Effects of elemental substitution involving V and Cr on superconductivity of (Tl,Bi)Sr2(Ca,Y)Cu2O7 ceramics - Hamid N.A.; Musa B.; Yahya A.K.; Jumali M.H.; Abd-Shukor R. (2023)
Cr and V substituted Tl1212 type phase high temperature superconductors with nominal starting compositions Tl0.9Bi0.1Sr 2-xCrxCa0.9Y0.1Cu2O 7 (x=0-0.5) and Tl0.9Bi0.1Sr 2-yVyCa0.9Y0.1Cu2O 7 (y=0-0.5) have been prepared and characterized. Powder X-ray diffraction patterns showed all samples consist of major 1212 phase and minor 1201 phase. For Tl0.9Bi0.1Sr2-xCr xCa0.9Y0.1Cu2O7, normal state resistance changes from metallic behavior (x=0-0.3) to semi-metallic behavior (x=0.4) and semiconductor-like behavior (x=0.5). Tczero gradually increased from 50K (x=0) to a maximum value of 78K at x=0.3 before decreasing with further Cr substitution. The x=0.5 sample was non-superconducting. For Tl0.9Bi0.1Sr2-yV yCa0.9Y0.1Cu2O7, normal state resistance changes from metallic behavior (y=0-0.3) to semi-metallic behavior (y=0.4) and semiconductor-like behavior (y=0.5). Tczero increased from 50K (y=0) to a maximum value of 76K (y=0.2) before decreasing to 62K (y=0.3). Samples with y=0.4 and 0.5 were non-superconducting. The effects of Cr and V substitutions are discussed in terms of ionic radius of dopants and the concept of average Cu valence. 2004 Elsevier Ltd. and Techna Group S.r.l. All rights reserved.